Examining the Impact of Product Quality, Consumer Experience, and Perceived Value on Customer Loyalty: a Structural Equation Modeling Approach - Mailoa, Betha Zionetha (Journal of Multidisciplinary Issues, 2024)
Purposes - This study aims to investigate the relationships between product quality, consumer experience, satisfaction, perceived value, and loyalty in the consumer goods market. Specifically, it seeks to understand how these variables contribute to fostering consumer loyalty, with a focus on identifying the direct and indirect effects of product quality, value, and experience on consumer loyalty. Methodology - A quantitative research approach was utilized, involving a survey-based data collection method. A structured questionnaire with a ten-point Likert scale was distributed to 250 respondents. The collected data were analyzed using Structural Equation Modeling (SEM) to test seven hypothesized relationships between product quality, value, experience, satisfaction, and loyalty. Findings - The results of the analysis indicate that product quality positively influences consumer experience, perceived value, and loyalty. Additionally, both satisfaction and perceived value were found to have significant positive effects on consumer loyalty. The findings highlight the importance of maintaining high product quality and creating positive consumer experiences to enhance long-term loyalty. Novelty - This research adds value by providing empirical evidence on the mediating roles of satisfaction and perceived value in the relationship between product quality and loyalty. It highlights the interconnectedness of these variables, offering a more comprehensive understanding of the mechanisms that drive consumer loyalty in the consumer goods sector. Research Implications - The findings of this study suggest that businesses should prioritize strategies that enhance product quality and consumer experience to foster loyalty. By focusing on these key areas, companies can effectively increase customer retention and strengthen their competitive position in the market. The study provides actionable insights for managers and marketers seeking to improve long-term consumer commitment.